2013
DOI: 10.2135/cropsci2012.08.0505
|View full text |Cite
|
Sign up to set email alerts
|

A Split Application Approach to Nitrogen and Growth Regulator Management for Perennial Ryegrass Seed Production

Abstract: Experiments were conducted during 2009 and 2010 in first year perennial ryegrass (Lolium perenne L.) fields under limiting or adequate spring N. Three N application methods (single, two‐split, and three‐split), five growth regulators (split and single applications of prohexadione Ca or trinexapac ethyl) and two spring N rates (56 or 100 kg N ha−1) were evaluated in a split‐split plot design. Under adequate spring N, all N application methods resulted in similar seed yields but when spring N was limiting, a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 39 publications
4
27
0
3
Order By: Relevance
“…Therefore, our analysis initially tested treatment effects across all environments along with the effect of environment (Table 1). Growing degree day accumulation, an important influence on agronomic characteristics in this region (Koeritz et al, 2013), began earlier during the 2010 harvest season (E1 and E2) than in the 2011 harvest season (E3 and E4) (Fig. Growing degree day accumulation, an important influence on agronomic characteristics in this region (Koeritz et al, 2013), began earlier during the 2010 harvest season (E1 and E2) than in the 2011 harvest season (E3 and E4) (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Therefore, our analysis initially tested treatment effects across all environments along with the effect of environment (Table 1). Growing degree day accumulation, an important influence on agronomic characteristics in this region (Koeritz et al, 2013), began earlier during the 2010 harvest season (E1 and E2) than in the 2011 harvest season (E3 and E4) (Fig. Growing degree day accumulation, an important influence on agronomic characteristics in this region (Koeritz et al, 2013), began earlier during the 2010 harvest season (E1 and E2) than in the 2011 harvest season (E3 and E4) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Growing degree day accumulation, an important influence on agronomic characteristics in this region (Koeritz et al, 2013), began earlier during the 2010 harvest season (E1 and E2) than in the 2011 harvest season (E3 and E4) (Fig. Previous observations have indicated that more N may be required for optimum perennial ryegrass seed yield at the site of E3 and E4 in this study (Kurcinka, 2009;Koeritz et al, 2013). The soil type for E1 and E3 (Roseau) was also different from the soil type for E2 and E4 (Roosevelt).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction in stem length and lodging by TE resulted in increased seed yield in perennial ryegrass (Lolium perenne L.) seed crops (Borm and van den Berg, 2008;Rolston et al, 2010;Koeritz et al, 2013;Chastain et al, 2014a). While the effects of TE on lodging control and seed yield in perennial ryegrass (Rolston et al, 2010;Koeritz et al, 2013;Chastain et al, 2014a) and strong creeping red fescue (Festuca rubra L. subsp. rubra) seed crops (Zapiola et al, 2006(Zapiola et al, , 2014 are well known, there have only been three investigations on these effects of TE in tall fescue.…”
Section: Introductionmentioning
confidence: 99%